KNOWLEDGE TRANSMISSION BY STORY TELLING Malaria Education of School-Aged Children in the Kwahu- Eastern Region, Ghana “ANANSI TRICKS MRS. MOSQUITO” - Gotfried, Edward A. (European Scientific Journal, ESJ, 2014)
We developed an educational tool to teach Ghanaian children the benefit of using malaria bed-nets to increase awareness/prevention of Malaria. Puppets, Comic books, and Videos demonstrated a visual approach constructed upon the ancient Ashanti art of “story telling”, using Anansi the Spider. Traditional or indigenous characters in stories make learning more enjoyable to children, guiding them towards comprehensive understanding. The knowledge achieved serves as a foundation for health education. Through myths and legends, we pass on our visions, values, feelings and memories in a way that is both enjoyable and entertaining. The best stories are those that motivate, inspire and connect – stories that make students feel some emotion and allow them to see themselves in similar situations. Students treasured the book, ANANSI TRICKS MRS. MOSQUITO. Older students read it to their younger siblings; elders in African societies encourage such teaching as transmission of knowledge.